Resilience and emotional regulation in parents of children with special needs (SN) - Veiga-Branco, Augusta (2017)
Parents of children with Special Needs (SN) experience higher levels of emotional distress (Lecavalier, et al, 2006), depression (Benson, 2006), anxiety (Pakenham, et al, 2004) and social isolation. Informal caregiving of a child with SN is often regarded as a moral duty and most often research has focused primarily on the deficits and risk factors among these families. Based on the current assumptions of Positive Psychology (Seligman, 2000), the current research focus on Family Resilience and Emotional Competence (Bisquerra, 2000; Veiga-Branco 2004, 2005, 2007), assuming the potentially healthy and positive aspects of families in opposition to traditional psychology and the need to promote emotional skills within families. This study aims to recognize the association between family resilience and emotional regulation in parents with children with SN. Quantitative and cross-sectional study, gathered by face to face survey, that will be conducted between the 15th of January and the 15 th of March of 2017 on a representative sample both parents of a child with SN from the northern and interior region of Portugal. Family resilience, dyadic coping and emotional competence of the couple were measured, respectively, by Portuguese versions of the Family Resilience Assessment Scale (Martins, et al., 2013), the Dyadic Coping Inventory (Vedes et al., 2013) and the Emotional Skills and Competence Questionnaire (Lima Santos & Faria, 2005). The relevance of the data obtained with families parenting children with special needs will be discussed considering the need of promoting resilience within these families.